Household access to traditional and indigenous foods positively associated with food security and dietary diversity in Botswana - Kasimba, Salome Nduku; Motswagole, Boitumelo Stokie; Covic, Namukolo; Claasen, Nicole (Cambridge University Press, 2018)
To determine access to traditional and indigenous foods (TIF) and the association with household food security, dietary diversity and women’s BMI in low socio-economic households.Sequential explanatory mixed-methods design, including a random household cross-sectional survey on household food insecurity access (HFIA), household dietary diversity (HDD) and women’s BMI, followed by focus group discussions.Two rural and two urban areas of Botswana.Persons responsible for food preparation or an adult in a household (n400); for BMI, non-pregnant women aged 18–49 years (n253).Almost two-thirds of households experienced moderate or severe food insecurity (28·8 and 37·3 %, respectively), but more than half of women were overweight or obese (26·9 and 26·9 %, respectively). Median HDD score was 6 (interquartile range 5–7) out of a total of 12. A positive correlation was found between number of TIF accessed and HDD score (r=0·457;P<0·001) and a negative correlation between number of TIF accessed and HFIA score (r=−0·272;P<0·001). There was no correlation between number of TIF accessed and women’s BMI (r=−0·066;P=0·297). TIF were perceived as healthy but with declining consumption due to preference for modern foods.TIF may potentially have an important role in household food security and dietary diversity. There is need to explore potential benefits that may be associated with their optimal use on food security and nutrition outcomes.